2018
DOI: 10.1186/s40246-018-0180-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genotype–phenotype association study reveals intronic variant pair on SIDT2 associated with metabolic syndrome in a Korean population

Abstract: BackgroundMetabolic syndrome is a risk factor for type 2 diabetes and cardiovascular disease. We identified common genetic variants that alter the risk for metabolic syndrome in the Korean population. To isolate these variants, we conducted a multiple-genotype and multiple-phenotype genome-wide association analysis using the family-based quasi-likelihood score (MFQLS) test. For this analysis, we used 7211 and 2838 genotyped study subjects for discovery and replication, respectively. We also performed a multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Gombojav et al identified in more than 8000 Korean individuals, several functional loci in 11q23.3 and found that SIDT2 is associated with an effect on plasma TG levels [ 14 ]. These data are consistent with the findings from Moon et al, who carried out a multiple genotype-phenotype association study in more than 10,000 Korean subjects and identified that the variant rs1784042 was associated with MetS and its components [ 16 , 52 ]. In addition, Kulminsky et al in a GWAS with more than 26,000 individuals from five longitudinal studies identified that the rs1784042 variant was associated with TC levels [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Gombojav et al identified in more than 8000 Korean individuals, several functional loci in 11q23.3 and found that SIDT2 is associated with an effect on plasma TG levels [ 14 ]. These data are consistent with the findings from Moon et al, who carried out a multiple genotype-phenotype association study in more than 10,000 Korean subjects and identified that the variant rs1784042 was associated with MetS and its components [ 16 , 52 ]. In addition, Kulminsky et al in a GWAS with more than 26,000 individuals from five longitudinal studies identified that the rs1784042 variant was associated with TC levels [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…The variant rs1784042, which is located within the SIDT2 gene on chromosome 11, was the strongest signal ( p GWAS = 0.006) for HDL-c ( Supplementary Figure S1 and Supplementary Table S4 ). The variant rs1784042 (A allele) has been recently associated with risk of MetS in a Korean population [ 16 ] and with high TG levels in cohorts from Nigeria and the Philippines [ 15 ], suggesting a potential association with MetS and related components in certain ethnic groups. In addition, due to the proximity to the variant rs1784042, we also included the missense variant p.V636I (rs17120425) and because, according to the 1000 genomes project, the rs17120425 is rare in several populations (MAF < 1.0%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a multiple-genotype and multiple-phenotype analysis of a genebased SNP set has been performed to identify new susceptible variants associated with MetS in 10,049 Korean individuals [29]. In this study, 27 SNP pairs were associated with MetS in the discovery stage and also replicated.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 72%